Penerapan kata ganda dalam kamus-kamus Melayu (Jurnal Bahasa, 2022)
This descriptive comparative study is to find out the similarities and differences in the use of reduplication forms in Wilkinson Dictionary, Winstedt Dictionary, Kamus Dewan (KD) and Kamus Besar Bahasa Indonesia (KBBI). The intertext approach in this study chooses this dictionaries as they are regarded as the most authoritative and renowned dictionaries which becomes a main source of references for vocabulary and linguistic inputs. This study is focused on two major aspects, namely the description of the reduplication forms in the Malay language, and the status of the reduplication forms in the dictionary either as a lemma, sublemma, pracategorial form, phrase, variant, or cross-reference. This also includes the parallel and non parallel forms which occurs in the headword and their derived forms, and loosely interpretation about the reduplication forms in the entry which is treated as a compound words. The meaning description deals with the semantic aspect of the reduplication forms to show whether they bear the lexical meanings or grammatical meanings. The meaning description reveals certain unique senses, particularly certain reduplication forms to show whether they bear the lexical meanings or grammatical meanings. The meaning description reveals certain unique senses, particularly certain reduplication forms which are associated and correlated in meanings that are different from the corpus. Based on various linguistic theories and corpus sources, this study tries to highlight certain issues that create some of the irregularities and dissimilarities encompassing the entry status. Hence, certain suggestions have been put forward so as to give some important and valuable inputs to the development of Malay lexicographic world, and at the same time to strengthen the language codification, particularly in elevating Malay/Indonesian monolingual dictionaries to the world class.